Experimental Study of Square CFST Stub Columns With a Low Steel Ratio Under Axial Loading - Lu, Deren; Gong, Yongzhi; Ding, Faxing; Wang, Liping; Deng, Chao; Yuan, Tao; Luo, Chen; Ren, Enhui (Frontiers in Materials, 2021)
This paper presents experimental and numerical study on large dimension concrete-filled square low steel ratio steel tubular (CFT) stub columns under axial loading. Four specimens were tested under axial loading to investigate the effects of steel ratio on the confinement effect of low steel ratio square CFT stub columns. ABAQUS was used to establish 3D finite element (FE) models for simulation of low steel ratio square CFT stub columns under axial loading. Furthermore, based on the experimental verification, the definition of the confinement index (ϕ=fsAs/ (fcAc)) was discussed and the effect of the grade of concrete and steel tube was also investigated. With the same cross-sectional dimensions, the restraint effect of the square CFT stub columns having steel ratio less than 0.05 was better than others and the specimen with steel ratio of 0.04 has the most constraining effect. In addition, the stub columns with yield strength of steel tube fs=235MPa (345MPa, 420MPa) and compressive cubic strength of concrete fcu=40MPa (60MPa, 80MPa) can give fully demonstrate to the material performance and reflect the better restraint effect. Based on the experimental results and FE modeling, a practical calculation formula for the ultimate bearing capacity of low steel ratio square CFT stub columns was proposed, the results obtained from the calculation formula presented in this paper were in good agreement with the experimental results and owe more accuracy than the existing calculation formulas.